Perlindungan Hukum terhadap Para Pihak dalam Perjanjian Kerja Sama Usaha Kuliner Perspektif Hukum Perikatan - Dikha Anugrah; Enggun Yoga Nugraha; Bisma Bintang Pradipta (Program Studi Ilmu Hukum, Universitas Kuningan, 2026)
The development of the culinary business sector in Indonesia has encouraged the increasing establishment of business partnerships among entrepreneurs, including capital investment, business management, and trademark utilization. Such partnerships create legal relationships based on civil agreements, making legal protection essential to ensure legal certainty for the parties involved. However, in practice, culinary business partnership agreements are often made in a simple manner and rely solely on mutual trust, creating the potential for disputes in the future. This study aims to analyze the legal protection afforded to the parties in culinary business partnership agreements from the perspective of the law of obligations, as well as the dispute resolution mechanisms arising from the implementation of such agreements. This research employs a normative juridical method using statutory and conceptual approaches through library research of primary and secondary legal materials. The findings indicate that legal protection is provided through the fulfillment of the legal requirements for a valid agreement, the application of the principles of freedom of contract, pacta sunt servanda, and good faith, as well as the regulation of contractual obligations and the legal consequences of breach of contract as stipulated in the Indonesian Civil Code. Disputes may be resolved through non-litigation mechanisms or litigation to ensure legal certainty and legal protection for the parties.